UTILIZATION OF PAPAYA SEEDS (CARICA PAPAYA L.) AS BIOCOAGULANTS TO IMPROVE THE QUALITY OF WELL WATER USING PARAMETERS OF pH, TSS, TDS, AND TURBIDITY - Euis Kusniawati; Rahma Nuryanti; Agricia Sindora Walici (Bajang Institute, 2023)
The increase in the amount of papaya production year after year is in line with the amount of papaya seed waste produced. Until now, papaya seed waste has not been widely used. Processing of papaya seeds as coagulants is one way to increase the value of papaya seeds, which until now has not been optimally utilized. This study aims to investigate the effect of using papaya seeds as coagulants and to determine the optimal size and dose of using papaya seeds to improve the quality of well water based on parameters pH, Turbidity, TSS and TDS. Based on the research that has been carried out, it showed that papaya seeds could be used as coagulants to purify water with an optimum dose of 0.5 grams, with particle size of 100 mesh, in 500 ml water sample. After given coagulants of papaya seeds, the increase in pH value obtained was 6.45, which was close to neutral. It could reduce turbidity up to 1.58 NTU, TSS 1 mg/L and TDS 30 mg/L.